Cosmology analogues in optical systems - Howard Eric (EPJ Web of Conferences, 2020)
We discuss the possibility of exploiting polariton-exciton physics as an analogue experimental tool to study challenging ideas and existing problems arising in the context of gravity theory and theoretical cosmology. We search for cosmology analogues with specific focus on simulating non-equilibrium dynamics across cosmological phase transitions in laboratory as well as employing optical analogue horizons in Bose-Einstein condensates (BECs) and signatures of white hole radiation to study gravitational and cosmological processes. Our analysis aims to uncover conceptual similarities between condensed matter systems and various phenomena in the Early Universe such as the symmetry breaking of the vacuum energy, spontaneous production of particles, false vacuum and cosmic inflation together with a number of unsolved cosmological problems.